JURIDICAL ANALYSIS OF SUPERVISION OF QUALITY SYSTEM IMPLEMENTATION IN FULFILLMENT OF EXPORT REQUIREMENTS FOR FISHERIES PRODUCTS TO REALIZE LEGAL PROTECTION TO THE COMMUNITY: RESEARCH STUDY AT THE OFFICE OF THE FISH QUARANTINE CENTER, QUALITY CONTROL AND SAFETY OF FISHERY PRODUCTS TANJUNGPINANG - Arrofik, Arrofik; Fadlan, Fadlan; Parroha Patar Siadari, Lagat (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
The construction of the journal topics mentioned above are: "Juridical Analysis of Supervision of Quality System Implementation in Fulfilling Export Requirements for Fishery Products to Realize Legal Protection to the Community (Research Study at the Tanjungpinang KIPM Center)", with the formulation of the problem: "How are the Legal Arrangements, Implementation, Constraint Factors, Barriers and Solutions in the Implementation of a Quality System in Fulfilling Export Requirements for Fishery Products at the Tanjungpinang KIPM Center?. This type of writing uses a descriptive method using a normative approach (legal research) to obtain secondary data and an empirical approach (juridical sociological), to obtain primary data through field research (field research). For the grand theory using positive law theory by John Austin, middle theory uses law enforcement theory proposed by Lawrence M. Friedman and applied theory uses legal compliance theory according to Soerjono, Salman and legal effectiveness theory according to Soerjono Soekanto. The results of the analysis concluded that the supervision of the implementation of the Fishery Product Quality Assurance System/HACCP by the competent authority of Balai KIPM Tanjungpinang was carried out through monitoring the implementation of activities and evaluating the achievements of surveillance activities on the consistency of the implementation of HACCP at UPI in accordance with the surveillance and official control programs.